2018
DOI: 10.4054/demres.2018.39.36
|View full text |Cite
|
Sign up to set email alerts
|

From hell to heaven? Evidence of migration trajectories from an Italian refugee centre

Abstract: BACKGROUNDIn recent years, large numbers of migrants have attempted to reach Europe by crossing the Mediterranean Sea. Italy plays a central role as a receiving country, particularly because of its relative proximity to the coast of North Africa. OBJECTIVEThis paper investigates the trajectories of migrants from their entry into a refugee centre to their departure, with evidence on the timing of the departure decision. METHODSUsing 2008-2014 data from a reception centre for refugees and asylum seekers located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Overall, we document a positive and statistically significant association between Internet diffusion in the country of origin (panel a) and voluntary departure from the Sant'Anna Cara reception center (hazard ratio, HR = 1.030) and seeking any form of protection (HR = 1.038). Previous work has shown that voluntary departure from the center is linked to a strong desire to leave Italy and reach another country, as Italy would only be the point of entry for several migrants who intend to reach another destination before even applying for international protection (Stranges and Wolff 2018). We thus interpret voluntary departure as an indicator of clarity of migration plans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, we document a positive and statistically significant association between Internet diffusion in the country of origin (panel a) and voluntary departure from the Sant'Anna Cara reception center (hazard ratio, HR = 1.030) and seeking any form of protection (HR = 1.038). Previous work has shown that voluntary departure from the center is linked to a strong desire to leave Italy and reach another country, as Italy would only be the point of entry for several migrants who intend to reach another destination before even applying for international protection (Stranges and Wolff 2018). We thus interpret voluntary departure as an indicator of clarity of migration plans.…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for departure include voluntary departure, obtaining any kind of protection (humanitarian protection, political asylum, subsidiary protection, temporary residence permit), and other reasons (including transfer to another reception center) 14 . Most of those who depart voluntarily from the center wish to reach another country in Europe (Stranges and Wolff 2018). Typically, irregular migrants engage, predeparture and postarrival, in intense information‐seeking—which may be further enhanced by the Internet—on questions such as (i) Where in Europe am I most likely to be granted refugee status?…”
Section: Methodsmentioning
confidence: 99%
“…First, the ORIM surveys covered only reception and support centres in one Italian region and cannot be considered nationally representative. Moreover, most asylum seekers arrive at the maritime border in the southern regions and only afterwards (if they do not voluntarily leave or escape the centres of first reception) are they transferred to the central and northern regions (Stranges & Wolff, 2018). Asylum seekers who arrive in Lombardy are, therefore, self-selected, now living in the wealthiest region of Italy.…”
Section: Con Clus I On S and Ne X T S Tepsmentioning
confidence: 99%
“…This study suggests that the dangerous journey is becoming a great equaliser; the likelihood of facing extremely adverse conditions is very high and shared across a spectrum of categories (such as sex, age and socio‐economic status) that migrants are frequently classified into. Data also suggest that the journey to Italy is becoming more dangerous for migrants across a range of categories, and that migration strategies could be shifting to long‐term plans and settlement in response to restrictions on onward movement that was prevalent in the first phases of the crisis (Stranges & Wolf, 2018). Those challenges – as well as limitations on onward mobility and the territorial selection of the sample – likely factor into why the majority of respondents intended to remain in Italy even in the face of negative experiences during the journey, high unemployment rates and growing anti‐refugee sentiments.…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
“…Among those who arrived in Italy fewer than three months before the interview, the majority were asylum-seekers, and were waiting to access the host system (about 90 per cent), others had escaped from the official reception centres (Stranges & Wolff, 2018). We found that of the individuals in the settlements who had been in Italy for three or more months, most were foreign nationals who were holders of international and humanitarian protection, but were outside the official reception system, including refugees (just over 20 per cent), holders of subsidiary protection (27.4 per cent), holders of residence permits for humanitarian reasons (22.8 per cent), asylum-seekers (5.7 per cent), individuals without any permit of stay (11.3 per cent), and other typologies (11.2 per cent).…”
Section: Informal Settlements and Their Inhabitantsmentioning
confidence: 99%